Health consequences during pandemic: a review - Mohd Azahar, Nazar Mohd Zabadi; Ahmad Zaki, Muhammad Amin; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
COVID-19 pandemic has brought many changes in daily life. The pandemic has affected all populations in the world and lead to WHO calling for the global action to minimize the spread of this infection. Social distancing, work from home and movement control order are some of the strategies implemented to mitigate this infectious outbreak. Health consequences on non-communicable disease, mental health, social crisis among schoolchildren and burnout among healthcare providers have been affected during the pandemic. This review will provide a brief explanation on these health consequences of COVID-19 to the population. Future strategies that can be implemented during pandemic will also be discussed in the review.